2021
DOI: 10.1111/jne.12931
|View full text |Cite
|
Sign up to set email alerts
|

Neurolysin substrates bradykinin, neurotensin and substance P enhance brain microvascular permeability in a human in vitro model

Abstract: Increased brain microvascular permeability and disruption of blood-brain barrier (BBB) function are among hallmarks of several acute neurodegenerative disorders, including stroke. Numerous studies suggest the involvement of bradykinin (BK), neurotensin (NT) and substance P (SP) in BBB impairment and oedema formation after stroke; however, there is paucity of data in regard to the direct effects of these peptides on the brain microvascular endothelial cells (BMECs) and BBB. The present study aimed to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…In a reverse experiment, which utilized viral vector-driven overexpression of Nln in the brain, a substantial attenuation of stroke outcomes, including brain infarction, neuroinflammation, vascular permeability, brain edema, and neurological impairment, was documented in animals . Notably, the observed cerebroprotective role of Nln has been linked to its fundamental function as a peptidase, suggesting that in the poststroke brain, Nln inactivates several cerebrotoxic neuropeptides [bradykinin (BK), neurotensin (NT), substance P, and angiotensin II] and generates at least three [angiotensin-(1–7), Met-, and Leu-enkephalins] cerebroprotective neuropeptides. , …”
Section: Introductionmentioning
confidence: 99%
“…In a reverse experiment, which utilized viral vector-driven overexpression of Nln in the brain, a substantial attenuation of stroke outcomes, including brain infarction, neuroinflammation, vascular permeability, brain edema, and neurological impairment, was documented in animals . Notably, the observed cerebroprotective role of Nln has been linked to its fundamental function as a peptidase, suggesting that in the poststroke brain, Nln inactivates several cerebrotoxic neuropeptides [bradykinin (BK), neurotensin (NT), substance P, and angiotensin II] and generates at least three [angiotensin-(1–7), Met-, and Leu-enkephalins] cerebroprotective neuropeptides. , …”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, the regulation of acid-sensing ion channels (ASICs) is altered during ischaemic stroke, contributing to neuronal death, and has been shown to depend on neuropeptide function (nocistatin, big dynorphin, and RFamide). Additionally, the upregulation of substance P, bradykinin, and neurotensin have all recently been reported to worsen stroke pathology by increasing BBB permeability [ 217 ], although their control and neutralization via actions of neurolysin appears to reduce resultant oedema [ 218 ]. Finally, studies have reported that polymorphisms in the NPY gene promoter may increase risk of ischaemic stroke [ 219 , 220 , 221 ], and upregulation of the neuropeptide has been suggested to contribute towards mechanisms underlying haemorrhagic stroke onset [ 222 ], whilst lower levels have been linked with post-ischaemic stroke epilepsy [ 223 ].…”
Section: Interrelation Between Neuropeptide Signalling Metabolic Dysr...mentioning
confidence: 99%
“…It has been previously proven that there are three neuropeptides, bradykinin (BK), neurotensin (NT), and substrate P (SP), that cause barrier weakening in ischemic stroke patients and there is now evidence that all three peptides have an impact on the permeability of the BBB. 125 In this study, two separate monolayers were explored, the first being the hCMEC/D3 cell line and then human induced pluripotent stem cell (iPSC)-derived brain microvascular endothelial cells, which were differentiated using conditioned media. Once properly cultured, both cell types were seeded on a TCPS and Transwell inserts which were coated with collagen and fibronectin to promote cell adhesion.…”
Section: Disease Modelingmentioning
confidence: 99%